Information design considerations in graphic artifacts of the diet prescription process: A study of information flow in a public university hospital - Cavalcanti Sampaio, Grace Maria; Spinillo, Carla (InfoDesign, 2022)
Problems with manual recording of information in graphic artifacts in hospitals can compromise the effectiveness of the nutritional care process (PCN), impairing the diet of patients. This article presents the mapping of the information flow of the PCN with a focus on graphic artifacts, as a sign of problems that may interfere with the quality of hospital nutrition services. To this end, a case study of the HC/UFPR hospital was carried out to identify potential problems in the graphic configuration of hand-filled artifacts that could make it difficult to record and read information. The results showed that documents generated in digital and printed systems have the addition of handwritten information, have deficiencies in their graphic configuration, and the problems caused by handwriting when filling in forms can compromise the continuity of the flow of information and, consequently, the activities necessary for the nutritional care of the patient. It is concluded that the principles and concepts of information design can collaborate in the organization and representation of information in the graphic artifacts of the PCN in hospitals and thus help the flow of information.